ANALISIS KOMPARATIF DESAIN PRODUK, BRAND TRUST, DAN HARGA PADA PRODUK SCOOTER MATIC MEREK HONDA DAN YAMAHA DI SIDOARJO - Mufaidah, Umrotul; Handayani, Sri; Pudjianto, Agung (Research Journal of Social Science and Economics, 2025)
This study aims to find out whether there are differences in product design, brand trust, and price for automatic scooter products for the Honda and Yamaha brands in Sidoarjo. The research method used in this research is quantitative research with comparative research. Comparative research is research that is used to compare between two or more groups of certain variables. This research was conducted by distributing questionnaires through the Google form to consumers who use Honda and Yamaha automatic scooters. In determining the sample the researcher used the non-probability sampling method, namely a sampling technique in which all members of the population have the same opportunity to be selected as samples with a total sample of 96 people. Using the data analysis method, the two-variant similarity test (homogeneity) aims to find out whether some population variants are the same or not and the independent sample t test aims to compare the averages of unrelated groups (unpaired). each other and assisted by SPSS Version 23. The results showed that there were differences in variance in the three variables of product design, brand trust, and price.